"Lucy" (A.L. 288‐1) had five sacral vertebrae. Issue 2 (21st October 2014) - Russo, Gabrielle A.; Williams, Scott A.
ABSTRACT A "long‐backed" scenario of hominin vertebral evolution posits that early hominins possessed six lumbar vertebrae coupled with a high frequency of four sacral vertebrae (7:12‐13:6:4), a configuration acquired from a hominin‐panin last common ancestor (PLCA) having a vertebral formula of 7:13:6‐7:4. One founding line of evidence for this hypothesis is the recent assertion that the "Lucy" sacrum (A.L. 288‐1an, Australopithecus afarensis) consists of four sacral vertebrae and a partially‐fused first coccygeal vertebra (Co1), rather than five sacral vertebrae as in modern humans. This study reassesses the number of sacral vertebrae in Lucy by reexamining the distal end of A.L.288‐1an in the context of a comparative sample of modern human sacra and Co1 vertebrae, and the sacrum of A. sediba (MH2). Results demonstrate that, similar to S5 in modern humans and A. sediba, the last vertebra in A.L. 288‐1an exhibits inferiorly‐projecting (right side) cornua and a kidney‐shaped inferior body articular surface. This morphology is inconsistent with that of fused or isolated Co1 vertebrae in humans, which either lack cornua or possess only superiorly‐projecting cornua, and have more circularly‐shaped inferior body articular surfaces. The level at which the hiatus' apex is located is also more compatible with typical five‐element modern human sacra and A. sediba than if only four sacral vertebrae are present. Our observations suggest that A.L. 288‐1 possessed five sacral vertebrae as in modern humans; thus, sacral number in "Lucy" does not indicate a directional change in vertebral count that can provide information on the PLCA ancestral condition. Am J Phys Anthropol 156:295–303, 2015. © 2014 Wiley Periodicals, Inc.